Effects of percutaneous renal sympathetic denervation on cardiac function and exercise tolerance in patients with chronic heart failure - Jun-Qing Gao; Yun Xie; Wei Yang; Jian-Pu Zheng; Zong-Jun Liu (Revista Portuguesa de Cardiologia, 2017)
Introduction: Sympathetic hyperactivity, a vital factor in the genesis and development of heart failure (HF), has been reported to be effectively reduced by percutaneous renal denervation (RDN), which may play an important role in HF treatment. Objective: To determine the effects of percutaneous RDN on cardiac function in patients with chronic HF (CHF). Methods: Fourteen patients (mean age 69.6 years; ejection fraction [EF] <45%) with CHF received bilateral RDN. Adverse cardiac events, blood pressure (BP), and biochemical parameters were assessed before and six months after percutaneous operation. Patients also underwent echocardiographic assessment of cardiac function and 6-min walk test before and at six months after percutaneous operation. Results: The distance achieved by the 14 patients in the 6-min walk test increased significantly from 152.9±38.0 m before RDN to 334.3±94.4 m at six months after RDN (p<0.001), while EF increased from 36.0±4.1% to 43.8±7.9% (p=0.003) on echocardiography. No RDN-related complications were observed during the follow-up period. In 6-month follow-up, systolic BP decreased from 138.6±22.1 mmHg to 123.2±10.5 mmHg (p=0.026) and diastolic BP from 81.1±11.3 mmHg to 72.9±7.5 mmHg (p=0.032). Creatinine levels did not change significantly (1.3±0.65 mg/dl to 1.2±0.5 mg/dl, p=0.8856). Conclusion: RDN is potentially an effective technique for the treatment of severe HF that can significantly increase EF and improve exercise tolerance. Resumo: Introdução: Foi reportado que a hiperatividade simpática, um fator vital para a génese e desenvolvimento da insuficiência cardíaca (IC), pode ser efetivamente reduzida pela desnervação simpática renal percutânea (DSR), que pode vir a desempenhar um papel importante no tratamento da IC. Objetivo: Determinar os efeitos da DSR por via percutânea na melhoria da função cardíaca em doentes com insuficiência cardíaca crónica (ICC). Métodos: Catorze doentes (idade média, 69,6 anos; fração de ejeção [FE], <45%) com ICC foram submetidos a RDN bilateral. Eventos cardíacos adversos, pressão arterial e índices bioquímicos foram realizados antes e seis meses após a intervenção. Os doentes também foram sujeitos a avaliação ecocardiográfica da função ventricular e ao teste de seis minutos de marcha, antes e seis meses após a intervenção. Resultados: A distância percorrida pelos 14 doentes no teste de seis minutos de marcha aumentou de forma significativa, de 152,9 ± 38,0 m antes DSR para 334,3 ± 94,4 m, seis meses depois da DSR (p<0,001), enquanto a FE aumentou de 36,0 ± 4,1% para 43,8 ± 7,9% (p=0,003) no ecocardiograma. Não foram relatadas complicações da DRS durante o período de follow-up. Num follow-up de seis meses, a pressão sistólica desceu de 138,6 ± 22,1 mmHg para 123,2 ± 10,5 mmHg (p=0,026) e a pressão diastólica de 81,1 ± 11,3 mmHg para 72,9 ± 7,5 mmHg (p=0,032), sem alteração dos valores de creatinina (de 1,3 ± 0,65 mg/dl para 1,2 ± 0,5 mg/dl, p=0,8856). Conclusão: A DSR é potencialmente uma nova e eficaz técnica para o tratamento da ICC severa, porque pode aumentar significativamente a FE e melhorar a tolerância ao exercício. Keywords: Renal denervation, Sympathetic nervous system, Heart failure, Blood pressure, Palavras-chave: Desnervação renal, Sistema nervoso simpático, Insuficiência cardíaca, Pressão arterial